Performance Analysis of Islamic Banks Using Error Correction Model - Addury, Multazam Mansyur; GH, Nur Hishaly; Izzaturrahman, Muh. Dzulfikar; Pangestu, Dian Resky (UIN Kiai Ageng Muhammad Besari Ponorogo, 2024)
Introduction: The analysis of Islamic banking performance is a frequent subject of discussion in various literature. One factor that makes Islamic banks an exciting object of research is their role as Sharia-based intermediary institutions and their contribution to the effectiveness of monetary policy. This study aims to analyze the impact of CAR, NPF, FDR, and BOPO on the performance of Islamic banks measured by ROA and NOM. Research Methods: This quantitative research uses secondary data from Islamic Banking Statistics covering the period from January 2015 to December 2023. The data analysis technique employed is the Error Correction Model (ECM). Results: The results indicate that out of the four variables examined, only BOPO has a significant impact on the performance of Islamic banks. Conclusion: This finding suggests that efficiency in managing operational costs is a crucial factor in enhancing the financial performance of Islamic banks. The lower the BOPO, indicating higher cost efficiency, the better the performance of Islamic banks in terms of profitability as measured by ROA and NOM.